Analysis of the defending possibilities against SQL Injection attacks - Byzdra, Chrystian; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2019)
The article describes various protection methods of database and types of SQL Injection attacks. These are extremely dangerous attacks because they threaten the confidentiality of sensitive data. In order to analyze in detail protection methods and methods of attacks, simulations of attacks and defence were performed in the following languages: C #, PHP, Java. Based on the simulation results for particular languages, the effectiveness and efficiency of database protection methods were compared.